Um génio português: Edmundo Curvelo (1913-1954) - José António Alves (Documentos, 2013)
This book presents the first study into the collection of Edmundo Curvelo (1913-1954), professor in the Faculty of Letters of the University of Lisbon and co-responsible for the introduction of psychotechnic and psychological laboratories into Portugal. Some of his philosophical manuscripts are published here for the first time, along with his correspondence with great names of 20th century Philosophy (W. V. Quine, Alonzo Church, Stephen Kiss, Joaquim de Carvalho and Delfim Santos). The book also contains a study which contextualizes Curvelo's oeuvre within the history of 20th-century Portuguese science and thought.